Association of folate with hearing is dependent on the 5,10-methylenetetrahdyrofolate reductase 677C → T mutation - Durga, Jane; Anteunis, Lucien J.C.; Schouten, Evert G.; Bots, Michiel L.; Kok, Frans J.; Verhoef, Petra (Neurobiology of aging, 2006)
Vascular disease and its risk factors have been associated with the age-related hearing loss. We examined the association of elevated plasma homocysteine and its determinants with hearing levels. Pure-tone air conduction thresholds in 728 individuals with sensorineural hearing loss were not associated with homocysteine, erythrocyte folate and Vitamin B 6. Low concentrations of serum folate and Vitamin B 12 were associated with better hearing. When folate status was below the median, 5,10-methylenetetrahydrofolate reductase (MTHFR) 677TT homozygotes had similar hearing levels to subjects with a C allele. However, when folate status was above the median, MTHFR 677TT homozygotes had on an average 5 dB ( p = 0.037) and 2.6 dB ( p = 0.021) lower PTA-high and PTA-low hearing thresholds, respectively, than the subjects with a 677C allele. The relationship between serum folate and hearing thresholds appeared to be dependent on MTHFR 677 genotype (CC, r = 0.13, p = 0.034; TT, r = –0.10, p = 0.291). This supports the hypothesis that a greater one-carbon moiety commitment to de novo synthesis of nucleotides and an increase in formyl-folate derivatives relative to methyl-folate derivatives is protective for hearing.